Synthesis and characterization of zinc oxide core-shell heterojunction nanowires grown by vapor deposition - Muhammad Arif Khan, 1980- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2017